An efficient motion adaptive de-interlacing algorithm using spatial and temporal filter - Byounghyun Yoo; Byungsung Kim; Kwaehi Lee (TENCON 2011 - 2011 IEEE Region 10 Conference, 2011)
A motion adaptive de-interlacing algorithm is widely used for de-interlacing technique. Generally, a spatial method with edge dependent interpolation (EDI) algorithm shows better results than any other de-interlacing algorithms using single field in motion region and a temporal filter which is using multi field shows good results in stationary region. The motion adaptive method uses both a spatial and a temporal method. However, it also has problems with applying in high frequency image due to some artifacts. In this paper, we propose a de-interlacing algorithm with a motion adaptive method using EDI and temporal filter. The algorithm consists of an improved motion detection, EDI-based spatial filter, and vertical temporal filter (VTF). This algorithm produces a good visual performances in the case of fast moving objects and complex textures. PSNR shows.